Conversion of waste cooking oil into biodiesel using heterogenous catalyst derived from cork biochar. (April 2020) - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Tae-Rim; Kim, Hyun Joong; Yang, Soo-Yeon; Song, Hun-Suk; Park, Jun Young; Park, Ye-Lim; Han, Yeong-Hoon; Choi, Yong-Keun; Kim, Sang-Hyoun; Yoon, Jeong-Jun; et al.
Graphical abstract: Highlights: Cork biochar produced at temperature 600 °C has porous structure. Conc. H2 SO4 activated biochar able to transesterify WCO into biodiesel. A:O ratio (25:1) at catalyst loading 1.5% w/v results in 98% FAME conversion. Produced biodiesel has CN (50.56), HHV (39.5), ʋ (3.9) and (ρ) 0.87. Abstract: In this study, a heterogeneous catalyst prepared by pyrolysis of waste cork (Quercus suber) was used for the transesterification of waste cooking oil (WCO). Physicochemical properties of the synthesized biochar catalyst were studied using BET, SEM, FTIR, and XRD. The experiment results demonstrate that heterogeneous catalyst synthesized at 600 °C showed maximum fatty acids methyl esters (FAMEs) conversion (98%) at alcohol:oil (25:1), catalyst loading (1.5% w/v) and temperature 65 °C. Biodiesel produced from WCO (Canola oil) mainly composed of FAMEs in following order C18:1 > C18:2 > C16:0 > C18:0 > C20:0. Properties of produced biodiesel were analysed as cetane number (CN) 50.56, higher heating value (HHV) 39.5, kinematic viscosity (ʋ) 3.9, and density (ρ) 0.87.